Can Social Ties Be Harmful? Examining the Spread of Suicide in Early Adulthood. (June 2015) - Mueller, Anna S.; Abrutyn, Seth; Stockton, Cynthia
Durkheim posited that social relationships protect individuals against suicide; however, substantial research demonstrates that suicide can spread through the very ties Durkheim theorized as protective. With this study, we use Waves I, III, and IV of the National Longitudinal Study of Adolescent Health to investigate whether young adults' suicide attempts and ideations are in part products of exposure to suicidal behaviors via their social relationships. We find that young adults who have had family members or friends attempt suicide are more likely to report suicide ideation or even suicide attempts over both the short and long run. This finding is robust to many important controls for risk and protective factors for suicide. Our findings have implications for the sociology of suicide, not the least of which is that social ties have the power to harm in addition to the power to protect.